Two Major Characters Differences as source of conflict in A Streetcar Named Desire - Diva Wenanda (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2013)
Character and conflict are the important elements in a play. Conflict is dominant aspect in this play. The structure of this play is best seen through a series of confrontation between Blanche DuBois and Stanley Kowalski. The conflict is social conflict. Blanche DuBois comes from aristocracy family, and Stanley Kowalski comes from lower class. The factors of the conflict are the background and character. The background differences are heritage, wealth, and education. The character differences can be traced from astrological aspect, color preference and light avoidance. The conflict between Blanche and Stanley is caused by their different worlds.